Analysis of Maqâshid Al-Sharî'ah on the Dutu Tradition in Hulondalo Tribe Wedding in Gorontalo - Reswin Mustapa; Muhtadin Dg Mustafa; Soraya Attamimi (State Institute for Islamic Studies Palu, 2022)
This study examined the dutu tradition procession at the wedding of the Hulandalo Gorontalo tribe in the perspective of maqâsid al-syarî`ah. This study used a qualitative method. The data was collected through direct observation, in-depth interviews, and written document analysis. The data, then, was analyzed using thematic analysis to find themes from the data. The results of this study show that, the procession of the dutu tradition at the wedding of the Hulandalo Gorontalo tribe goes through stages called the wedding process in which the whole community performs (lenggota lo nika) or the standard order of Gorontalo tribal marriages. It has become a tradition that has been passed down from generation to generation and becomes mandatory before the marriage process takes place. The dutu tradition is a tradition that has elements that refer to the Qur'an and the Sunnah of the Prophet. The family tradition is good to carry out and will also be beneficial for human life in the future where in the processes of this dutu tradition contains a lot of sacred meaning. Our analysis of maqâsid al-syarî`ah in the traditions of the marriage dutu of the Hulondalo tribe showed that it belongs to the category of maqashidhajiyyat which maintains its maqashiddharuriyyat. Marriage is a form of hifzalnasl, which Allah commands. The high delivery price is in the position of maqashidtahsîniyyat to glorify a woman as a form of maintaining religion, soul, intellect, offspring, and property. This study concludes that the people of Gorontalo hope that giving Dutu (dowry) is not a burden for a man to marry a woman and that giving gifts is adjusted to the man's ability. The obligation to give gifts is to pleases all parties both mean and women families.